Особенности восприятия идеологем приверженцами различных политических течений - Мищенко, М. (Социология: теория, методы, маркетинг, 2000)
The level of supporting the ideologems used in political life of Ukrainian society is
investigated in the paper, as well as peculiarities of conceiving those ideologems by the
adherents of various political trends.
The procedure of factor analysis is used in studying the structure of the respondents’
ideological orientations.
The effect of the peculiarities of the ideologems perception as one of the factors which
determine the electorate behavior is studied in the wide sociological context.